"Hoping to strike some sort of solidity":: The Shifting Fictions of Alistair MacLeod - Creelman, David (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
If Alistair MacLeod repeatedly examines similar themes and issues in his two collections of short stories, it would be a mistake to assume that they are built on the same philosophic or ideological paradigm. Compared to the persistent note of skepticism, doubt, and uncertainty which characterizes The Last Salt Gift of Blood, the later stories in As Birds Bring Forth the Sun and Other Stories signal a clear and confident epistemological shift toward certainty. MacLeod's early texts are ultimately driven by a strong ideological commitment to a liberal humanist vision of the independent individual. The protagonists in the later stories discover and secure their identities only by fusing themselves with the larger community.